“Andorinha, Lindóia e Mimosa”: a importância da pecuária leiteira para os agricultores familiares das comunidades rurais Canoa e Baixadão no município de Ituiutaba (MG) - Fratari, Marina Franco (2019)
The 1990s were a milestone for family agriculture in Brazil, with the creation of the National Program for Strengthening Family Agriculture (PRONAF). Impacted by the modernization of the Brazilian agrarian space since the 1970s, family farming faced many difficulties in acquiring new technologies to increase and specialize production, access to credit and financing, as well as the commercialization of its products. At the same time, the milk production chain underwent many changes in the same period, absorbing new technologies and greater specialization of producers. Livestock farming is an economic activity present in the state of Minas Gerais since its colonization, both cattle ranching and dairy farming are responsible for employment and income in the countryside, the state has the second largest cattle herd in the country (IBGE, 2015). Dairy farming is the main source of income for family farmers in the rural communities Canoa and Baixadão, in Ituiutaba (MG). The main objective of this research is to comprehend the reality of dairy farming developed by family farmers, through their reproductive strategies in the context of the modernization of milk production, its relation with milk agroindustries and the dilemmas for its resistance in this activity. Seeing the object of study that is the family livestock, in this study the bibliographical and documentary research was carried out; the collection, tabulation and analysis of primary and secondary source data and information, as well as field research. The inclusion of new technologies and management techniques in dairy production, such as the mechanical milking machine and the expansion tank, has been verified in the rural communities surveyed, although the producers still report many difficulties in obtaining human and technical resources to improve milk production. In the last five years sugar cane plantations have also increased in the communities, which has contributed to the leasing of properties, especially of the less capitalized producers, who see in the rent of their lands for sugar cane agroindustries, a source of income more profitable than milk production. Therefore, there is uncertainty about the future on the part of these family producers, who in debt continue trying to modernize milk production and thus ensure their survival and their families in the countryside.